In vitro apoptotic and antiproliferative effects of propranolol on human breast cancer cells: Propranolol induces apoptosis in breast cancer cells (Indian Journal of Experimental Biology (IJEB), 2024)
Breast cancer is an issue of concern with increasing incidence among women worldwide. Propranolol, as an antihypertensive drug, exerts anticancer effects too. We conducted this study to analyze the in vitro apoptotic and anti proliferative effects of propranolol in human MCF-7 breast cancer cells. MCF-7 cells were seeded into 6-well plates and treated with 50 µL propranolol for 24 hours. After cell homogenization, the levels of pro-apoptotic proteins BCL2 associated X (BAX), apoptosis inducing factor (AIF), C/-EBP homologous protein (GADD153), and glucose-regulated protein 78 (GRP78), anti-apoptotic protein BCL2 apoptosis regulator (BCL-2), and cycle-regulator WEE1 G2 checkpoint kinase (WEE1) were measured with ELISA. Propranolol significantly upregulated pro-apoptotic proteins AIF, BAX, GADD153, and GRP78 while downregulated anti-apoptotic protein BCL2. The level of WEE1, as the main regulatory cell cycle protein at the G2/M checkpoint, significantly increased after propranolol treatment. Propranolol inhibited the proliferation of MCF-7 human breast cancer cells by upregulating pro-apoptotic factors AIF, BAX, GADD153 and GRP78 and by downregulating antiapoptotic BCL2. Elevated WEE1 levels after propranolol treatment might lead the tumor cells into a sustained cell-cycle arrest which eventually resulted in caspase-dependent or -independent mitochondrial or endoplasmic-reticulum stress-induced apoptosis. So, propranolol can be utilized as a potential therapeutic agent in breast cancer therapy.